Los verbos de memoria ’recordar’ y ’acordarse’ en el español mexicano: Entre la gramática y la cognición - Valdes Saucedo, Cecilia (Borealis – An International Journal of Hispanic Linguistics, 2026)
ABSTRACT. This article studies the verbs recordar and acordarse in contemporary Mexican Spanish through corpus analysis to identify a systematic correlation between the verbs’ syntactic structures, cognitive nuances and the pragmatic-discursive functions of these verbs in press and literary discourse. The analysis is based on the theoretical framework of syntactic bootstrapping and verb class studies. The results reveal that these verbs are very similar when they share the same semantic nucleus related to episodic memory, since in both verbs aspectual versatility and the ability to refer to volitional or non-volitional processes are recorded. On the other hand, in the pragmatic component recordar and acordarse performed complementary functions, carrying out a division of linguistic labor. Recordar focused on functions that had an impact on the receiver, acting as a mechanism of persuasion and discursive authority, as well as a positioning tool for the speaker, enabling them to “evaluate” or express “objectively” the nature of certain information as false or true. Acordarse mainly presented functions oriented toward the sender, allowing him to express an evaluative opinion about something or acting as a polite mechanism to protect his image, either to express their personal and subjective opinion about something or as a polite mechanism to protect their image.